Common LeSS Transformation Patterns - Heřmánek, Jakub; Buchalcevová, Alena, 1958-; Doležel, Michal; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2022)
The diploma thesis focuses on large-scale agile transformations. The thesis aims to conduct a narrative literature review of LeSS agile framework adoption case studies to simplify the information-gathering process for future adopters. It consists of three primary parts. The first part sets the theoretical framework for the following part. A narrative literature review of primary sources is conducted using the NLP and human evaluation of the case studies. The last part compares the answers to the research questions regarding LeSS framework agile adoption with the results presented by the 15th state of agile report, which offers readers a general overview of agile adoption around the globe.
Vedoucí práce: Alena Buchalcevová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: podniková informatika [obor dipl. práce]; diplomové práce; master's theses